Implementasi Pembelajaran Aswaja dalam Pembentukan Perilaku Keagamaan dan Sosial Peserta Didik di SMP Ma’arif 1 Metro - Agustina, Agustina; Aziz Q, Ikhwan; Arifin, M. Zainal (Attractive : Innovative Education Journal, 2024)
Aswaja is a method of looking at various problems in people's lives and thoughts (Minhaj al-Fikr). Nahdlatul Ulama members are guided by this view to act and behave in accordance with religious teachings. This research tries to find out how aswaja learning is implemented in shaping the religious and social behavior of students at SMP Ma'arif 1 Metro. This research takes a qualitative approach in data collection, using methods such as documentation studies, interviews and observations. Research findings show that by deepening the subject matter and daily practice, Aswaja NU learning carried out both inside and outside the classroom helps shape students' social and religious behavior. The inhibiting factor for Aswaja NU learning at SMP Ma'arif 1 Metro is the lack of reading literature. Aswaja is a method of looking at various problems in people's lives and thoughts (Minhaj al-Fikr). Nahdlatul Ulama members are guided by this view to act and behave in accordance with religious teachings. This research tries to find out how Aswaja NU learning is implemented, what influences it, and what factors help or hinder in influencing students' religious behavior and social behavior at SMP Ma'arif 1 Metro. This research takes a qualitative approach in data collection, using methods such as documentation studies, interviews and observations. Research findings show that by deepening the subject matter and daily practice, Aswaja NU learning carried out both inside and outside the classroom helps shape students' social and religious behavior. The inhibiting factor for Aswaja NU learning at SMP Ma'arif 1 Metro is the lack of reading literature Keywords: Implementation Learning Aswaja, Formation of Religious Behavior, Social Behavior